Reshaping public accountability: hospital reforms in Germany, Norway and Denmark - Mattei, P; Mitra, M; Vrangbæk, K; Neby, S; Byrkjeflot, H (SAGE Publications, 2013)
The article contributes to the literature on multi-level welfare governance and public accountability in the context of recent European hospital reforms. Focusing on the changing dynamics between regional and central governance of hospitals in Germany, Norway and Denmark, we raise concerns about the reshaping of traditional public accountability mechanisms. We argue that, triggered by growing financial pressures, corporatization and professionalization have increasingly removed decision-making power from regional political bodies in hospital funding and planning. National governments have tightened their control over the overall trajectory of their hospital systems, but have also shifted significant responsibility downwards to the hospital level. This has reshaped public accountability relationships towards more managerial or professional types embedded within multi-level forms of governance.Points for practitionersOur study may be taken to suggest that if reforms are responses to policy pressures, the accompanying changes in accountability relationships and arrangements in turn contribute to altering the pressures and constraints that form the context for administrative, managerial and professional work. As reforms in Norwegian, Danish and German healthcare contribute to corporatization, centralization and economization, there is reason to expect that what officials are held accountable for, and how, is also likely to change and to accentuate the span between policy aims and actual managerial and professional performance.